Analisa Karakteristik Pembakaran Biopelet Berbahan Limbah Kelapa Muda Dengan Penambahan Variasi Zeolit Alam - Rozi, Muhammad Fahrur; Nusantara, Ardhi Fathoni syam Putra; Bahri, Mokh. Hairul (Journal of Engineering Science and Technology, 2023)
Biomass is a type of solid waste that is used as an alternative energy source to replace fossil fuels (petroleum) because it can be renewed. Biopellets are a renewable fuel that comes from biomass. The aim of this research is to determine the characteristics of coconut waste biopellets. young with the addition of zeolite variations. The research method used is experimental research. The zeolite material used has 6 dosage variations, namely 0% (0 gram), 5% (2.5 grams), 10% (5 grams), 15% (7.5 grams) , 20% (10 grams), 25% (12.5 grams), with fixed variations from 50 grams of young coconut waste, tapioca flour adhesive and 20 grams of sugar cane molasses. The best burning rate of young coconut waste biopellets was obtained with the T 5 biopellet composition with a molasses adhesive composition with the addition of 5% zeolite with a value of 0.017% g/s. and the lowest water content value is found with the T 25 biopellet composition using molasses adhesive with a 25% zeolite mixture. And the best ash content value can be with P 0 biopellet composition using tapioca flour adhesive without zeolite mixture with a value of 3.32%.